Autologous platelet-rich gel for refractory plantar ulcer following ethanol sclerotherapy of peripheral venous malformation: a Case Report - Zhao, Zhenyu; Wu, Shaohui; He, Xiaoyan; Zhang, Yan; Chen, Xuemei; Tang, Jie (Frontiers in Bioengineering and Biotechnology, 2025)
Platelet-rich plasma (PRP) contains a high concentration of growth factors that promote angiogenesis, granulation-tissue formation and re-epithelialization, thereby significantly accelerating wound healing. Autologous platelet-rich gel (APG), a gelled form of PRP, provides a sustained release of these factors within a fibrin scaffold. We report a 25-year-old woman who developed a refractory plantar ulcer with tendon exposure after combined absolute-ethanol sclerotherapy and surgical excision of a congenital venous malformation of the left foot. Reflux of the sclerosant produced microcirculatory compromise, followed by full-thickness skin necrosis. Because the plantar skin is under high tension and has a relatively poor blood supply, conventional skin grafting was deemed unlikely to succeed. APG was therefore employed as a salvage treatment. After three applications, the ulcer area had decreased by 95%, and complete epithelialization was achieved within 1 month without scar contracture. Both functional and cosmetic outcomes were excellent. This case illustrates that APG promotes granulation and re-epithelialization of intractable ulcers following sclerotherapy for venous malformations, which reducing the need for grafting and representing a valuable adjunct for wounds with tendon exposure and compromised perfusion.